Maternal, fetal and perinatal factors associated with necrotizing enterocolitis in Sweden. A national case-control study - Ahle, Margareta; Drott, Peder; Elfvin, Anders; Andersson, Roland E. (PLOS ONE, 2018)
Objective To analyze associations of maternal, fetal, gestational, and perinatal factors with necrotizing enterocolitis in a matched case-control study based on routinely collected, nationwide register data. Study design All infants born in 1987 through 2009 with a diagnosis of necrotizing enterocolitis in any of the Swedish national health care registers were identified. For each case up to 6 controls, matched for birth year and gestational age, were selected. The resulting study population consisted of 720 cases and 3,567 controls. Information on socioeconomic data about the mother, maternal morbidity, pregnancy related diagnoses, perinatal diagnoses of the infant, and procedures in the perinatal period, was obtained for all cases and controls and analyzed with univariable and multivariable logistic regressions for the whole study population as well as for subgroups according to gestational age. Results In the study population as a whole, we found independent positive associations with necrotizing enterocolitis for isoimmunization, fetal distress, cesarean section, neonatal bacterial infection including sepsis, erythrocyte transfusion, persistent ductus arteriosus, cardiac malformation, gastrointestinal malformation, and chromosomal abnormality. Negative associations were found for maternal weight, preeclampsia, maternal urinary infection, premature rupture of the membranes, and birthweight. Different patterns of associations were seen in the subgroups of different gestational age. Conclusion With some interesting exceptions, especially in negative associations, the results of this large, population based study, are in keeping with earlier studies. Although restrained by the limitations of register data, the findings mirror conceivable pathophysiological processes and underline that NEC is a multifactorial disease.